Іноземні громадяни у військових формуваннях СС нацистської Німеччини (1939–1945 рр.) - Гетьманчук, Микола; Hetmanchuk, Mukola (Lviv Politechnic Publishing House, 2019)
Проаналізована політика нацистської Німеччини щодо створення та використання іноземних збройних формувань СС у роки Другої світової війни. Висвітлено мотиви й цілі перебування іноземних громадян у військових формуваннях СС. Особливу увагу приділено проблемі комплектування іноземними громадянами дивізій військ СС, їх місця у агресивних планах нацистського керівництва Третього Рейху.

The issue of the participation of foreign citizens in the SS military groups of Nazi Germany during the SecondWorld War has been studied. It has been shown that foreign citizens, who served in the SS forces, were conditionally divided according to racial and national principle and functional purposes. According to racial and national criteria, foreign citizens in the SS were divided into separate categories: 1) the first category – ethnic Germans – “Volksdeutsche”, as opposed to the German citizens – the imperial Germans – “Reichsdeutsche”; 2) the second category – the so-called “Germanic” peoples – English, Deutsch, Norwegians, Danes, Flemish, Swedes; 3) the third category of foreigners, the most numerous one, consisted of representatives of peoples of the former Soviet Union and the Baltic States; 4) the fourth category of foreigners – citizens of all other countries of Europe, Asia, Africa, and the Middle East. Three groups can be distinguished among them according to the motivation of their admission to the SS troops. The first one included foreign volunteers, who joined the SS troops mainly on ideological grounds. The second group was made up of foreigners from the territories annexed to Germany, who were mobilized into the SS forces. The third group consisted of prisoners of war from the armies of the Anti-Hitler coalition, who forcibly or voluntarily served in the SS. During the Second World War, Hitler and his entourage harnessed nationalism and general fear of Bolshevism that dominated in Europe. They realized that for the proclaimed Crusade against Bolshevism participation of all peoples of Europe is vital. Therefore, foreign military groups of the SS, according to the Nazi leadership, should have become: 1) the basis for the creation of a new “European Army”; 2) the embodiment of the concept of the development of a confederative “New united Europe”; 3) a powerful means for the creation of the European Reich after the victory over the world communism; 4) an important source of replenishment of SS military units with personnel. Two allied armies for Germany were created organizationally at the end of the war with the help of the SS – Russian and Slovenian. The study of the problem suggests that SS troops were traditionally considered not only to be the elite of the German Army during the Second World War, but also a unique phenomenon in military history. During the Second World War, 38 SS units, individual brigades, legions and special-purpose SS units were formed that were not part of the German Wehrmacht and the police. Among them, only 20 SS divisions, including the ethnic Germans – “volksdeutsche”, can be considered purely German. During 1939–1945, according to the researchers’ estimates, 530 thousand foreign citizens served in the SS forces: the ethnic Germans “volksdeutsche” – 180 thousand; representatives of the peoples of the former USSR – 150 thousand; Dutch – 25 thousand; French – 10 thousand; Italians – 10 thousand; Danes – 6 thousand; Hungarians – 41 thousand; Croats – 28 thousand; Romanians – 5700; Serbs – 9 thousand; Albanians – 9275; Indians – 3 thousand, etc. By the end of the war, the number of foreign nationals in SS troops was significantly higher than the number of imperial Germans. Most foreign divisions of SS troops were used only on the Eastern Front. Only three foreign SS divisions participated in the battles with the Allied troops on the Western Front – 34 – a (Dutch), 29 – a (Italian), 30 – a (Russian). Another four foreign SS divisions created in the Balkans (7, 13, 21, 23) and the Serbian Volunteer Corps of SS took part exclusively in the fight against the guerrilla movement. It has been emphasized in the historiography of the SS forces that the units that were created fromWestern European citizens proved to be the most combat-effective. At the same time, it has been stressed that the level of combat capability was determined by the motivation of the personnel.
Foreigners citizens in military formations of the SS Nazist Germany (1939–1945)
Keywords: Друга світова війна; Третій Рейх; колабораціонізм; війська СС; іноземні добровольці СС; Second World War; Third Reich; SS troops; collaborationism; foreign SS volunteers; 94 (100); 355. 318. 2 (430)